Finansial Analysis of Wanayasa Tilapia Culture in Mekarsari Farmer Group - Diatin, I.; Sobari, Moch. P.; Irianni, I. (Jurnal Akuakultur Indonesia, 2007)
This research aims to discover the general overview of the Nila Wanayasa's seeding business which conduct by Mekarsari's Conductors Group in Tanjungsari Village, to analyze the business' rent, to analyze the investment eligibility and to analyze the sensitivity of the price fluctuation of production factors, in this case is feed.  The business eligibility and its sensitivity judged by investment criteria i.e. NPV, Net B/C, and IRR.  The result shows the NPV is IDR 225,116,401.83, Net B/C is 19.38, and IRR is 707%.  The sensitivity analysis which using the switching value methods shows that the business is eligible to be continued with increasing price of feed until 800.917%, because of the NPV is zero, Net B/C is 1, and IRR is equal to the rate.  Keywords:  financial analysis, NPV, Net B/C, IRR, Nila Wanayasa's Culture   ABSTRAK Penelitian ini bertujuan untuk mengetahui kelayakan ekonomi usaha budidaya ikan nila Wanayasa yang dilakukan oleh kelompok tani Mekarsari, Desa Tanjungsari, Purwakarta.  Kriteria kelayakan usaha dan faktor sensitivitas yang diamati meliputi NPV, B/C net, dan IRR.  Hasil penelitian menunjukkan bahwa nilai NPV adalah sebesar Rp 225.116.401,83, B/C net sebesar 19,38, dan IRR 707%.  Analisa sensitivitas menggunakan metode "switching value" menunjukkan bahwa usaha petani layak dilanjutkan sampai harga pakan meningkat  800,92%, karena nilai NPV adalah nol, B/C net 1, dan IRR sama dengan tingkat suku bunga yang berlaku. Kata kunci:  analisis finansial, NPV, B/C, IRR, Nila Wanayasa